IMPLEMENTATION OF THE POLICY OF PUBLIC ROADSIDE PARKING RETRIBUTION BASED ON PERDA NO. 2 TAHUN 2012 IN KROBOKAN URBAN-VILLAGE SEMARANG CITY - Mutiarani Kusuma Aninda; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Public roadside parking levy policy is one of the efforts of the Semarang city to solve the parkings problem, which is to transport and the arrangement of public roadside wild parking and the achievement of the edge parking retribution Public roads. Semarang City as one of the major cities in Indonesia is required to manage and maximize the potential of indigenous revenue Sources (PAD). The purpose of this study is to analyze the implementation of public roadside parking levy policy in Krobokan village of Semarang City, and also the factors that affecting the implementation process of the policy. This research is a study with qualitative descriptive methods. The results showed that the implementation of the policy related to parking retribution in the Krobokan Village is still not optimal. Supporting factors of the roadside parking retribution public policy implementation process in the Krobokan Village is the executor good understanding who has mastered the policy well, and good communication intertwined between the implementing agents and other parties relating to the public roadside parking retribution policy. However, the limitation of the number of executor and resources of facilities, and the lack of direct monitoring in the field led to the implementation of the public roadside parking levy policy in the city of Semarang, especially around Krobokan village became less Optimal.